Fast and large area fabrication of hierarchical bioinspired superhydrophobic silicon surfaces. Issue 9 (August 2016) - Ghio, Simone; Paternoster, Giovanni; Bartali, Ruben; Belluti, Pierluigi; Boscardin, Maurizio; M. Pugno, Nicola
Abstract: In this work we present a new method to generate hierarchical surfaces, inspired by lotus leaf, on a silicon substrate. Mimicking leafs with particular properties, such as low adhesion, water repellence and self-cleaning, is an interesting case of study in the branch of bioinspired materials. These properties arise from a combination of surface chemistry and topography. The lotus leaf surface exhibits a highly controlled specific roughness, which has been studied and imitated by several researchers. The great challenge that has still to be solved is to reproduce lotus-inspired surfaces rapidly and on large areas. Our method consists in a combination of wet and dry etch with soft lithography, able to generate nano- and micro- hierarchical structures on silicon surfaces. Two different kinds of hierarchical structures are generated by changing the order of the etch steps. The surfaces generated were then characterized by measuring both the contact angle and the sliding angle. Finally, to validate experimental results, analytical models were implemented to predict the contact angle. The best surface displayed wetting performances superior even to those of the natural lotus leaf, thanks to the hierarchical structure, with a contact angle of 171° and a tilt angle of 4° with production time of about 90 min per silicon wafer, or 30 s/cm 2 .